Determining the affinities of high-affinity antibodies using KinExA and surface plasmon resonance - M. Frank Erasmus; Molly Dovner; Fortunato Ferrara; Sara D’Angelo; André A. Teixeira; Camila Leal-Lopes; Laura Spector; Elizabeth Hopkins; Andrew R. M. Bradbury (mAbs, 2023)
ABSTRACTAccurate and efficient affinity measurement techniques are essential for the biophysical characterization of therapeutic monoclonal antibodies, one of the fastest growing drug classes. Surface plasmon resonance (SPR) is widely used for determining antibody affinity, but does not perform well with extremely high affinity (low picomolar to femtomolar range) molecules. In this study, we compare the SPR-based Carterra LSA and the kinetic exclusion assay (KinExA) for measuring the affinities of 48 antibodies generated against the SARS-CoV-2 receptor-binding domain. These data reveal that high-affinity antibodies can be generated straight from selections using high-quality in vitro library platforms with 54% correspondence between affinities measured using LSA and KinExA. Generally, where there was a 2-fold or greater difference between LSA and KinExA, KinExA reported that affinities were tighter. We highlight the differences between LSA and KinExA, identifying the benefits and pitfalls of each in terms of dynamic range and throughput. Furthermore, we demonstrate for the first time that single-point screening with KinExA can significantly improve throughput while maintaining a strong correlation with full binding curve equilibrium measurements, enabling the accurate rank-ordering of clones with exceptionally tight binding properties.